Successful Implementation of a Change in Practice to Optimize Timing of Umbilical Cord Clamping in Preterm Neonates: A Quality Improvement Initiative. (1st June 2016) - Irvine, L; Abou Mehrem, A; Singhal, N; Thomas, S; Cooper, S
Abstract: BACKGROUND: Natural, also known as delayed, umbilical cord clamping (NCC) is recommended for at least 60 seconds (s) in preterm infants. However, changing the institutional guidelines only may not result in satisfactory adoption and change in practice. OBJECTIVES: To determine if a structured multidisciplinary educational approach during the implementation of the new guideline of NCC in pre-term infants will result in over 50% compliance rate. DESIGN/METHODS: The evidence supporting NCC was presented in a grand round to all health care providers involved in maternal-newborn care. A multidisciplinary team comprised of neonatologists, obstetricians, neonatal nurse practitioners, respiratory therapists and nurses developed NCC clinical practice guideline. Local champions at each of the 4 city hospitals were identified to create change in culture and establish lines of open communication between disciplines. Following completion of education of all staff involved in delivery room care, formal implementation of NCC began October 2013 for gestational age (GA) 33-35 weeks, January 2014 for GA ≥28 weeks, and April 2014 for GA ≥26 weeks. Data were collected from October 2013 until April 2015. RESULTS: Table 1 shows the compliance rates and the proportion of infants who received NCC ≥45s. In addition, we found that 18% of infants 26-32 weeks GA deemed eligible for NCC, received cord clamping at <45s to facilitate resuscitation. CONCLUSION: Compliance with practice change can be successfully achieved through a structured team approach, establishing open lines of communication, and frequent feedback to the front line members. Further research may lead to more infants qualifying for and resuscitated during NCC.